Prothrombin as Co-Factor of the Circulating Anticoagulant in Systemic Lupus Erythematosus? - Loeliger, A; with the technical assistance of Miss; Alsbach, E. J. J (Thrombosis and Haemostasis, 1959)
A 35-year old man with lupus erythematosus of the skin is demonstrated, who also shows signs of systemic L. E.: sometimes slightly increased ESR, varying thrombocytopenia, slightly prolonged coagulation and prothrombin time, positive cepnalin-cholesterol flocculation test, biologically false positive syphilis reactions and signs of a slightly increased haemolysis. Electrophoretic examination of the serum proteins presents practically normal values, certainly no hypergammaglobulinaemia. Analytical examination of coagulation reveals hypoprothrombinaemia and an anticoagulant most probably directed against thrombocyte factor 3, intrinsic thromboplastin and tissue thromboplastin. The anticoagulant seems to be only active in the presence of prothrombin. Prothrombin therefore, is considered a co-factor of the anticoagulant. The inactive anticoagulant is localized in the gamma globulins. The possible cause of the hypoprothrombinaemia (immune reaction?) and the data in the literature are discussed.